Boundaries in Kinematic Alignment: Why, When, and How - Indelli, Pier Francesco; Petralia, Giuseppe; Ghirardelli, Stefano; Valpiana, Pieralberto; Aloisi, Giuseppe; Salvi, Andrea Giordano; Risitano, Salvatore (The Journal of Knee Surgery, 2024)
The use of alternative alignments in total knee arthroplasty (TKA) has recently been increasing in popularity: many of these alignments have been included in the broad spectrum of “kinematic alignment.” This alternative approach was recommended to increase patients' satisfaction since many studies based on patient-reported outcome measures (PROMs) showed that every fifth patient is not satisfied with the surgical outcome. In fact, the original kinematic alignment technique was designed as a “pure resurfacing” technique, maintaining the preoperative axes (flexion–extension and axial rotation) of the knee. In adjunct, many new classifications of the preoperative limb deformity have been proposed to include a large range of knee anatomies, few of them very atypical. Following those classifications, many surgeons aimed for a reproduction of unusual anatomies putting in jeopardy the survivorship of the implant according to the classical “dogma” of a poor knee kinematics and TKA biomechanics if the final hip–knee–ankle (HKA) axis was not kept within 5 degrees from neutral. This article reviews the literature supporting the choice of setting alignment boundaries in TKA when surgeons are interested in reproducing the constitutional knee anatomy of the patient within a safe range.
Keywords: boundaries; alignment; kinematic alignment; TKA; arthroplasty; phenotypes